Implementation of the Experiential Learning Model: an Alternative Solution to Improve Chemistry Learning Outcomes of Vocational Students - Vidiastuti, Ririn; Hartono, Hartono (Jurnal Pendidikan Progresif, 2018)
Implementation of experiential learning model: an alternative solutions to improve chemistry learning outcomes in the vocational field. Objectives: This classroom action research was aimed to improve students’ chemistry learning result through experiential learning model.Methods: The study was conducted in two cycles, each cycle consisting of two meetings. Findings: Improvement of student learning outcomes can be seen from the mean score of student learning outcomes before the action done (T0) of 71,23 with mastery learning 42,86%, an increase in 1st cycle (T1) to 77,74 with mastery learning 62.86% and in 2nd cycle (T2) increased to 84,23 with learning mastery 85.71%. Keywords: Classroom action research, experiential model, chemistry learning outcomes DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201812